Dr. Susan Shillinglaw - Christine Macias:::Creator::::::::::::
Doctor Susan Shillinglaw in the Martha Heasley Cox Center for Steinbeck Studies at its 3rd location in California State University, SJ portables. This location was used through 2003-08 during the construction of the Dr. Martin Luther King, Jr. Library. Digital copy only; no hard copy.